Profiling and targeting HER2-positive breast cancer using trastuzumab emtansine - Sadeghi S; Olevsky O; Hurvitz SA (Dove Medical Press, 2014)
Saeed Sadeghi, Olga Olevsky, Sara A Hurvitz Division of Hematology & Oncology, David Geffen School of Medicine, University of California, Los Angeles, CA, USA Purpose: This article reviews the mechanism of action of trastuzumab emtansine (T-DM1), existing clinical data relating to its use for human growth factor receptor 2 (HER2)-positive breast cancer, potential pathways of resistance, and ongoing studies evaluating this novel agent.Background: The development of HER2-targeted therapies has dramatically improved clinical outcomes for patients with any stage of HER2-positive breast cancer. Although the positive effect of these treatments cannot be overstated, treatment resistance develops in the vast majority of those diagnosed with stage IV HER2-positive breast cancer. Moreover, HER2-directed therapies are most effective when combined with cytotoxic chemotherapy. The need for chemotherapy leads to significant adverse effects and a clear decrease in quality of life for those dealing with a chronic incurable disease. T-DM1 is a recently developed, novel antibody–drug conjugate in which highly potent maytanisinoid chemotherapy is stably linked to the HER2-targeted monoclonal antibody, trastuzumab.Results: Preclinical and phase 1–3 clinical data support the significant antitumor activity of T-DM1. Importantly, several randomized studies also now demonstrate its clear superiority in terms of tolerability compared with standard chemotherapy-containing regimens. Its role in the treatment of trastuzumab-resistant metastatic breast cancer has now been established on the basis of the results of two phase 3 randomized studies, EMILIA (An Open-label Study of Trastuzumab Emtansine (T-DM1) vs Capecitabine + Lapatinib in Patients With HER2-positive Locally Advanced or Metastatic Breast Cancer) and TH3RESA (A Study of Trastuzumab Emtansine in Comparison With Treatment of Physician's Choice in Patients With HER2-positive Breast Cancer Who Have Received at Least Two Prior Regimens of HER2-directed Therapy). The most common toxicities seen with T-DM1 are thrombocytopenia and an elevation in liver transaminases. Significant cardiac toxicity has not been demonstrated. Both in vitro cell line–based studies as well as exploratory analyses of archived tumor samples from the clinical trials are seeking to understand potential mechanisms of resistance to T-DM1. Ongoing studies are also evaluating the use of T-DM1 in the first-line metastatic, neoadjuvant, and adjuvant settings, as well as in combination with other targeted therapies.Conclusion: T-DM1 represents the first successfully developed antibody drug conjugate for the treatment of HER2-positive advanced breast cancer.Keywords: HER2, T-DM1, trastuzumab emtansine, ado-trastuzumab emtansine, metastatic breast cancer, Kadcyla